THE RELATIONSHIP OF LEAD EXPOSURE RISK TO AGGRESSIVE BEHAVIOR - Soriton, Jimmy Nixon (Jurnal Penelitian Kesmasy, 2025)
Lead exposure is a concern that must be addressed by many stakeholders in Indonesia. Lead exposure results in many health problems. With its status as a cumulative toxic substance, lead has the ability to cause a number of significant negative effects on overall public health. Lead exposure has long been suspected as one of the causes of aggressive behavior. However, the underlying mechanism of this impact is not completely understood. Public awareness, especially adolescents, of sources of exposure and assessment of adolescent aggressive behavior is very important because prolonged exposure to lead will prevent adolescents from realizing their potential. The purpose of this study was to conduct an article review focusing on the association between lead exposure and aggressive behavior. Articles were gathered by doing a systematic search of electronic databases such as Google Scholar, PubMed, and MDPI, with publication dates limited to 2019-2023. The keywords utilized were lead, exposure, aggressive behavior. The findings of this literature review indicate a robust link between lead exposure and aggressive behavior in a variety of age groups and populations. In general, the study methods utilized in the selected articles, utilizing both longitudinal cohort and cross-sectional designs, indicated that greater blood or bone lead levels were associated with increased aggression.. Keywords: Lead, Exposure, Behavior, Aggressive